Процена на внатрешно налегнување и маргинална дискрепанца кај целосно керамички и металкерамички коронки - Василева Гешовска, Катерина (Стоматолошки факултет, УКИМ, Скопје, 2018)
The precision of the internal and marginal fit of the crowns is important criteria for the clinical quality, success and longevity of prosthetic dental restoration. Crowns serve to establish lost function and aesthetics without compromising the oral or general health of patients. Inappropriate fitting of crowns is potentially harmful to the prepared tooth and the periodontal tissues. Passing through and adhering of oral bacteria causes secondary caries, gingival irritation and hypersensitivity. Aesthetics, fracture resistance, and marginal accuracy are the main determinants of dental crowns. Therefore, as the main purpose of this study is to examine the internal and marginal accuracy of all-ceramic and metal-ceramic dental crowns. Considering that this is an in vitro study, a 32-teeth dental replica model was used, and five of them were prepared with a standardized diamond bur. Impressions were taken with a conventional two-phase method using polyvinyl siloxanes, and digital impressions with the Apollo DI Sirona intraoral scanner. Three different methods of manufacturing technology were used: hot pressed ceramics - IPS e.max press Lithium disilicate, computer aided design, computer aided production - CAD/CAM of zirconium blocks and Ni-Cr alloy casting. Six groups of 15 crowns were made. Replica technique is the method that we applied for the testing of the fit of crowns. Microscopic measurements were made with a microscope, 3-dimensional measuring machine. Then the mean values were calculated and through statistical processing we got the results. Applied statistical tests are the Mann-Whitney test, Analysis of Variance-ANOVA, and the PostHoc Tukey HSD test. Compared to conventional impressions, digital impressions has proven to be a more precise method, creating crowns whose marginally fit is quite precise. The lowest average values of two measuring points in the margin of the digital impressions has the digital impression/zirconium crowns and they are 0.110 ± 0.08 and 0.080 ± 0.2. The lowest average values in the margin for conventional impressions is found in conventional impression/е max crowns and they are 0.130 ± 0.06 and 0.115 ± 0.04. The highest average value of measuring points in the margin of the digital impressions have the digital impression/Ni-Cr alloy crowns and they are 0.22 ± 0.05 and 0.16 ± 0.1. The highest value in conventional impressions is found in conventional impression/Ni-Cr alloy crowns and it amounts 0.308 ± 0.2 on the first and 0.378 ± 0.2 on the second measuring point. Internal fit of crowns was also examined on several measuring points and it showed better fitting with those produced with digital impressions. Average values showed most intimate fitting in digital impression/zirconium crowns. Comparisons were made between the two groups, digital and conventional impresions, as well as comparisons between the six subgroups. There are differences between groups, some are significant, some are non-significant, but what has been measured is that digital impressions has proved to be more precise than conventional, and that digital impression/zirconium crowns have the lowest values and have the best fitting on prepared tooth.
Докторска дисертација одбранета во 2018 година на Стоматолошкиот факултет во Скопје, под менторство на проф. д–р Јагода Бајевска.